The origins of food: The not so Thai Pad Thai - Khoury, Colin K.; Valiño, Álvaro; Nowakowski, Kelsey (2019)
In the late 1930s, the leader of Thailand introduced the dish to his country in an effort to define a national identity and improve nutrition. The Thai government distributed the recipe and encouraged vendors to sell it throughout the country. Ironically, the dish’s iconic chiles aren’t very tied to Thailand.